Isoform-Specific Effects of Apolipoprotein E on Hydrogen Peroxide-Induced Apoptosis in Human Induced Pluripotent Stem Cell (iPSC)-Derived Cortical Neurons - Huiling Gao (MDPI AG, 2021)
Hydrogen peroxide (H2O2)-induced neuronal apoptosis is critical to the pathology of Alzheimer’s disease (AD) as well as other neurodegenerative diseases. The neuroprotective effects of apolipoprotein (ApoE) isoforms against apoptosis and the underlying mechanism remains controversial. Here, we have generated human cortical neurons from iPSCs and induced apoptosis with H2O2. We show that ApoE2 and ApoE3 pretreatments significantly attenuate neuronal apoptosis, whereas ApoE4 has no neuroprotective effect and higher concentrations of ApoE4 even display toxic effect. We further identify that ApoE2 and ApoE3 regulate Akt/FoxO3a/Bim signaling pathway in the presence of H2O2. We propose that ApoE alleviates H2O2-induced apoptosis in human iPSC-derived neuronal culture in an isoform specific manner. Our results provide an alternative mechanistic explanation on how ApoE isoforms influence the risk of AD onset as well as a promising therapeutic target for diseases involving neuronal apoptosis in the central nervous system.